DETERMINATION OF STRESS INTENSITY FACTOR FOR HETEROGENEOUS FOR BASIC STATE OF STRESS - Рудяк, Ю.А. (Proceedings of National Aviation University (archive), 2012)
The solution of spatial problems of fracture mechanics destruction by optical methods for low levels of optical anizotropic was examined. It is important for basic stress intensity factor. The experimentally calculation method was worked out. The formula for stress intensity factor was determined.